2021
DOI: 10.34087/cbusbed.856434
|View full text |Cite
|
Sign up to set email alerts
|

Koroner Arter Cerrahisinin Solunum Fonksiyonlarına Etkilerinin Solunum Fonksiyon Testi İle Değerlendirilmesi

Abstract: Kronik Obstrüktif Akciğer Hastalığı (KOAH), koroner arter bypass greft operasyonu (CABG) yapılan hastalarda sık bir komorbid hastalıktır ve insidansı %4 ile %20,5 aralığındadır. KOAH geleneksel olarak CABG için cerrahi kontraendikasyon olarak bilinir. Cerrahi teknik, anestezi ve postoperatif hasta yönetimindeki son gelişmelerden dolayı CABG artık KOAH'lı hastalarda çok yaygın bir şekilde yapılmaktadır. Ancak son çalışmalar, CABG sonrası postoperatif mortalite ve morbidite üzerine KOAH'ın çeşitli etkilerini gös… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…A different study reported no difference between the two groups regarding these two parameters [27]. COPD is a common comorbid disease in patients undergoing coronary artery bypass graft surgery [28]. In our study, COPD was more common in the MECC group.…”
Section: 2discussioncontrasting
confidence: 42%
“…A different study reported no difference between the two groups regarding these two parameters [27]. COPD is a common comorbid disease in patients undergoing coronary artery bypass graft surgery [28]. In our study, COPD was more common in the MECC group.…”
Section: 2discussioncontrasting
confidence: 42%